Allocating scarce intensive care resources during the COVID-19 pandemic: practical challenges to theoretical frameworks - Supady, Alexander; Curtis, J. Randall; Abrams, Darryl; Lorusso, Roberto; Bein, Thomas; Boldt, Joachim; Brown, Crystal E.; Dürschmied, Daniel; Metaxa, Victoria; Brodie, Daniel (The lancet. Respiratory medicine, 2021)
The COVID-19 pandemic strained health-care systems throughout the world. For some, available medical resources could not meet the increased demand and rationing was ultimately required. Hospitals and governments often sought to establish triage committees to assist with allocation decisions. However, for institutions operating under crisis standards of care (during times when standards of care must be substantially lowered in the setting of crisis), relying on these committees for rationing decisions was impractical—circumstances were changing too rapidly, occurring in too many diverse locations within hospitals, and the available information for decision making was notably scarce. Furthermore, a utilitarian approach to decision making based on an analysis of outcomes is problematic due to uncertainty regarding outcomes of different therapeutic options. We propose that triage committees could be involved in providing policies and guidance for clinicians to help ensure equity in the application of rationing under crisis standards of care. An approach guided by egalitarian principles, integrated with utilitarian principles, can support physicians at the bedside when they must ration scarce resources.
Gesehen am 15.06.2021